2010
DOI: 10.1093/europace/euq418
|View full text |Cite
|
Sign up to set email alerts
|

Use of an implantable loop recorder to increase the diagnostic yield in unexplained syncope: results from the PICTURE registry

Abstract: AimsTo collect information on the use of the Reveal implantable loop recorder (ILR) in the patient care pathway and to investigate its effectiveness in the diagnosis of unexplained recurrent syncope in everyday clinical practice.Methods and resultsProspective, multicentre, observational study conducted in 2006–2009 in 10 European countries and Israel. Eligible patients had recurrent unexplained syncope or pre-syncope. Subjects received a Reveal Plus, DX or XT. Follow up was until the first recurrence of a sync… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
143
2
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(166 citation statements)
references
References 22 publications
16
143
2
5
Order By: Relevance
“…Diagnosis rates in the TC group are very similar to those described in previous studies (28% [11], 24% [12]) with similar populations. However, the lack of previous studies in the patient population from SC does not allow making any comparisons.…”
Section: Results Of the Ilrsupporting
confidence: 88%
See 2 more Smart Citations
“…Diagnosis rates in the TC group are very similar to those described in previous studies (28% [11], 24% [12]) with similar populations. However, the lack of previous studies in the patient population from SC does not allow making any comparisons.…”
Section: Results Of the Ilrsupporting
confidence: 88%
“…The prevalence of structural heart disease in our population (30%) was similar to that in previous studies (28-33%), and so were the rest of baseline characteristics [11,12]. We did not find significant differences between patients from TCs and SCs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…4 The authors concluded that an ELR may be indicated for the initial screening of patients with recurrent unexplained syncope or presyncope in place of a more expensive ILR, which remains an option if, after 1 month, monitoring with an ELR has proven negative. 13 The International Study on Syncope of Uncertain Etiology (ISSUE-1) study showed that the majority of syncopal events documented with an ILR is likely to be neurally mediated, with asystolic pauses and reflex bradycardia being the most frequently associated rhythm disturbances.…”
Section: Loop Recorders In Syncope and Palpitationsmentioning
confidence: 99%
“…For the most part ILRs have proven to be of greatest value in determining an arrhythmic basis for syncope, 1,2) and on occasion have been helpful in demonstrating that certain patients believed to be suffering from epilepsy, but whose symptoms are 'drug-refractory', may in fact be suffering from syncope.…”
mentioning
confidence: 99%